Acute suppurative thyroiditis with transient hyperthyroidism in thalassemia child: an uncommon association in a common disease-a rare case report - Swaranjika Sahoo; Basudev Biswal; Anuspandana Mohapatra; Rachita Sarangi (SpringerOpen, 2020)
Abstract Background Thyroid infection is rare in paediatric age group in anatomically normal thyroid gland. However, acute suppurative thyroiditis (AST) is common in high-risk cases like thyroglossal duct remnant and thyroglossal pyriform sinus fistula. This may be associated with variable thyroid dysfunctions. Though transient hyperthyroidism is reported in some cases, its association was not documented in thalassemia child. Case presentation We are reporting an 8-year-old male child with a history of fever, pain, and left neck swelling for 5 days. He was evaluated and empirically started intravenous antibiotics (ceftriaxone, cloxacillin, and amikacin) along with other supportive treatment for localized signs of thyroid infection. Ultrasonography of the neck revealed intercommunicating pockets of collections with internal echoes in the left thyroid lobe. CT neck was done and suggested that the left lobe of the thyroid gland was replaced by hypodense lesions of fluid attenuation without any congenital abnormality of the thyroid gland. His thyroid function tests were suggestive of biochemical hyperthyroidism. He was treated with intravenous antibiotics and ultrasonography-guided fine-needle aspiration of pus. His pus culture showed growth of methicillin resistant Staphylococcus aureus. He also had microcytic hypochromic anaemia which was evaluated and found to have thalassemia trait. His biochemical hyperthyroidism normalized after completion of 2 weeks of treatment and required no intervention. Conclusion Acute suppurative thyroiditis is an uncommon clinical condition in an anatomically normal thyroid gland which could be associated with thyroid dysfunction. Its association in a thalassemia child is also not documented in literature. Clinical evaluation and proper history taking and non-invasive thyroid imaging are the cornerstone for diagnosis. Antibiotics and pus drainage are the mainstay management. Associated biochemical hyperthyroidism is transient and resolves without any specific medication in asymptomatic cases.